Novel polymer-based hydrogels of recent research in drug delivery for disease treatment related to SARS-CoV-2 virus - Nguyen Hoc Thang; Nguyen Van Phuc; Tran Thi Tu Nhi; Dang Xuan Cuong; Do Quang Minh (eXPRESS Polymer Letters)
Polymer-based hydrogels are hydrophilic polymer networks with a remarkable capacity to absorb substantial amounts of water and biological fluids, rendering them highly attractive for drug delivery applications. The COVID-19 pandemic has acted as a catalyst for research and innovation in the realm of polymer-based hydrogels for drug delivery, with a particular emphasis on antiviral therapeutics, vaccines, diagnostics, and precision delivery to the respiratory system. The distinctive attributes of hydrogels, such as their biocompatibility, customizable drug release profiles, and ease of functionalization, establish them as versatile platforms for the development of advanced drug delivery systems to combat not only COVID-19 but also a spectrum of other infectious diseases. This study is dedicated to scruti-nizing and evaluating the characteristics of polymer-based hydrogels employed in drug delivery for the treatment of diseases associated with the SARS-CoV-2 virus. Furthermore, the investigation introduces a novel classification system for polymer-based hydrogels deployed in drug delivery for SARS-CoV-2-related diseases. Additionally, the paper provides an up-to-date evaluation of the latest developed hydrogels utilized in drug delivery for the treatment of dis-eases linked to the SARS-CoV-2 virus, based on research conducted through the recent months of 2023.